The Commelinaceae of Madhya Pradesh - Tiwari, S. D. N.; Maheshwari, J. K. (Indian Forester, 1965)
The paper deals with an enumeration of the spiderworts of Madhya Pradesh. A total number of 26 species belonging to the genera Commelina Linn., Cyanotis D. Don nom. Cons., Floscopa Lour., Murdannia Royle nom. Cons., Rhoeo Hance, and Zebrina Schnizl., is described in this paper.